Changing of the coordination of socioeconomic development and the environment as sustainable development progresses - Dongliang Dang; Xiaobing Li; Xin Lyu; Shiliang Liu; Huashun Dou; Mengyuan Li; Kai Wang; Wanyu Cao (Geography and Sustainability)
The relationship between socioeconomic development and the environment is intimately linked with the level of regional sustainable development. Clarifying the evolution pattern of this relationship during the sustainable development progress is crucial for achieving all of the Sustainable Development Goals (SDGs), but less research has focused on this problem. Here, we have utilized statistical and remote sensing data from 290 municipal units in China to analyze the evolution of the coupling coordination degree (CCD) between socioeconomic development and the environment along a progression of sustainable development measured by the SDG Index. The results show that the hotspot areas of CCD are concentrated in coastal regions, gradually decreasing as they move inland. Additionally, as sustainable development progresses, both socioeconomic and environment levels exhibit a nonlinear rise. The coupling coordination between the two demonstrates a pattern of initial increasing, then decreasing, and finally increasing again, which may be related to changes in industrial structure. Our study delves deeply into the patterns of evolution in the relationship between socioeconomic and environments, exploring the challenges and opportunities faced by regions at different stages of sustainable development. The findings can deepen our understanding of sustainable development and provide policy suggestions and theoretical support for achieving SDGs.